Preliminary results of a single-arm pilot study to assess the safety and efficacy of visnadine, prenylflavonoids and bovine colostrum in postmenopausal sexually active women affected by vulvovaginal atrophy. (March 2018) - Laganà, Antonio Simone; Vitale, Salvatore Giovanni; Stojanovska, Lily; Lambrinoudaki, Irene; Apostolopoulos, Vasso; Chiofalo, Benito; Rizzo, Laura; Basile, Francesca
Highlights: Vulvovaginal atrophy (VVA) is very common after the menopause. A single-arm pilot study of local visnadine, prenylflavonoids and bovine colostrum was undertaken. Improvement of symptoms of vulvovaginal atrophy was found after 15 days of treatment in 47 women. Randomised controlled trials are now required. Abstract: This single-arm pilot study enrolled 47 post-menopausal women affected by vulvovaginal atrophy (VVA). The Vaginal Health Index Score (VHIS) was evaluated for all women and all completed the Female Sexual Function Index (FSFI) questionnaire at baseline (T0) and after 15 days of vaginal cream treatment with one application per day (T1). Following treatment there was a significant improvement in all VHIS parameters and total score (p < 0.0001). Similarly, there was a significant improvement on four FSFI domains (lubrication, orgasm, satisfaction and pain) and total score (p = 0.001). None of the patients reported any local or systemic side-effects during treatment.